Aplikasi Rekam Medis Kesehatan Balita dalam Menentukan Kesehatan Balita di Rw 002 Sicalung - Fardhoni Fardhoni; Andinna Ananda Yusuff (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
The industrial revolution in medical and health industry developed rapidly. With the consequence in rapid grow of big data usage, the development of data decentralization becomes more important, because it can facilitate more accurate analysis. The problem in this study is data collection and monitoring of the health of toddlers and early childhood in Posyandu (integrated healthcare center) is still inaccurate while they still used manual data input and has not been carried out in real time, therefore we created medical record application that able to provide convenience in monitoring the health of toddlers and early childhood, as well to analyze their development in term of heath. The results of the testing showed that mothers expect toddlers to be well controlled. The implementation of the toddler health medical record application provides convenience and real time report and analysis in Posyandu for midwives, health care provider and for mothers as well. Suggestions for further research is to combine with other methods so that future applications will be perfectly polished to be used widely.